"I am willing to do both well": Chinese academic mothers facing tension in family and career. - Bao, Li; Wang, Guanghua (Frontiers in psychology, 2022)
Academic mothers perform intersected roles. They carry out their profession in workplaces, while they take the "second shift" of motherhood back to their families. The contested expectations in family and career built by the heterosexual matrix cause tension to academic mothers. We qualitatively investigate the interview data of six Chinese women academics on how they perform to negotiate their motherhood and academic work in the context of Chinese higher education, driven by the Butlerian theoretical concept of the heterosexual matrix. The findings suggest that Chinese academic mothers play a zero-sum game between being mothers and being academics, deriving from their ontological responsibilities of motherhood. We conclude that in the masculine academia, these women academics help maintain the heterosexual matrix by satisfying the gender normativity when they negotiate their performances in their family and career; meanwhile, most have developed some strategies to achieve their career advancement.; Competing Interests: The authors declare that the research was conducted in the absence of any commercial or financial relationships that could be construed as a potential conflict of interest. (Copyright © 2022 Bao and Wang.)
Keywords: 2000 à aujourd'hui; 2020-2029; approches et analyses; asie; chine; conciliation famille-travail; famille; femmes* universitaires; hétérosexisme; maternité; matrice hétérosexuelle; projet charge mentale; périodes historiques; ressource en ligne; régions géographiques; sexisme; systèmes d'oppressions; thématiques; travail

“I have no room of my own”: COVID-19 pandemic and work-from-home through a gender lens - Chauhan, Priyanshi (Gender Issues, 2022)
Working from home is not gender neutral. As the COVID-19 pandemic has relocated all non-essential work to the home setting, it becomes imperative to examine the phenomenon through a gender lens. Accordingly, I conducted a qualitative study using semi-structured interviews with 30 dual-earning married couples in India to study the gendered work-from-home experiences of men and women during the pandemic. The findings suggest that the pandemic has disproportionately increased the burden of unpaid work for women as compared to men. Women are negotiating gendered time–space arrangements within their households with the allocation of limited resources being in favor of men. When this interacts with work, gender inequalities are reinforced both at work and home. Gender roles and unpaid work determine women’s choices regarding when and where to work, boundary management between work and non-work domains, and their experiences of social isolation. Further, gender roles have also affected women’s decisions regarding returning to work post-pandemic, where some women may not be returning to work at all. Finally, the paper identifies how gender intersects with the existing conceptual frameworks of working from home, and makes a strong case for integrating gender considerations in the work-from-home policies. © 2022, The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature.
Keywords: 2000 à aujourd'hui; 2020-2029; approches et analyses; asie; conciliation famille-travail; covid-19; famille; hétérosexisme; inde; inégalités; inégalités hommes-femmes; pandémie; projet charge mentale; périodes historiques; régions géographiques; systèmes d'oppressions; thématiques; travail; travail gratuit

Gender inequities in household labor predict lower sexual desire in women partnered with men - Harris, Emily A; Gormezano, Aki M.; van Anders, Sari M. (Archives of Sexual Behavior, 2022)
Low sexual desire in women is usually studied as a problem, one that is located within women. However, other possibilities exist, including known gender inequities related to heteronormative gender roles. In this study, we provide the first test of the theory that heteronormativity is related to low sexual desire in women partnered with men, focusing specifically on inequities in the division of household labor. In two studies with women who were partnered with men and had children (Study 1, N = 677; Study 2, N = 396), performing a large proportion of household labor was associated with significantly lower sexual desire for a partner. Together, the results suggest that this association was mediated by both perceiving the partner as a dependent and perceiving the division of labor as unfair. These results support the heteronormativity theory of low sexual desire in women partnered with men, and show that gender inequities are important, though understudied, contributors to low desire in women partnered with men. © 2022, The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature.
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; désir; hétéronormativité; hétérosexisme; projet charge mentale; périodes historiques; santé; sexualité; systèmes d'oppressions; thématiques; travail; travail domestique

Pas ce soir, chéri, j’ai mal à la tête (parce que je fais ton lavage) - Massicolli, Elisabeth (Gazette des femmes, 2022)
Quel est le lien entre la charge mentale et l’épanouissement sexuel des femmes au sein des couples hétérosexuels? On fait le point. Dans le livre Women Who Run With the Wolves, la psychanalyste Clarissa Pinkola Estés écrit : « Il y a cette drôle de chose à propos du nettoyage de la maison… c’est que c’est une tâche qui n’est jamais terminée. C’est la façon parfaite d’empêcher une femme de faire quoi que ce soit d’autre. » L’autrice parle ici du processus créatif : elle affirme que l’art ne peut pas être pratiqué que dans des moments « volés », entre une brassée de lavage et la préparation du souper. Que l’art prend du temps et que l’artiste doit agir avec ses pulsions et, pour y arriver, être en mesure de se reposer.
Keywords: 2000 à aujourd'hui; approches et analyses; charge mentale; conciliation famille-travail; famille; hétérosexisme; projet charge mentale; périodes historiques; ressource en ligne; sexisme; sexualité; stéréotypes de genre; systèmes d'oppressions; thématiques; travail; travail domestique

Don’t give mum chocolates for Mother’s Day. Take on more housework, share the mental load and advocate for equality instead - Ruppanner, Léa (The Conversation, 2022)
Keywords: 2000 à aujourd'hui; approches et analyses; care; charge mentale; charge émotionnelle; discipline; hétérosexisme; patriarcat; projet charge mentale; périodes historiques; ressource en ligne; sciences humaines; sociologie; systèmes d'oppressions; thématiques; travail; travail invisible